Effect of Heavy Metals and Risk Analysis on Arable Farmlands in Selected Local Government Areas of Southern Taraba State, Nigeria - Habibu, Bilyaminu; Olawale, Otitoju; Ejeh, Yakubu Ojochenemi; Umaru, Isaac John; Oko, John Odiba; Ezeonu, Chukuma Stephen; Odufa, Egbeadumah Maryanne (Darul Yasin Al Sys, 2024)
Heavy metals are naturally occurring metallic elements that have a relatively high density compared to water. In most of the continent including Africa, the lack of food quality usually stand to be one of the major problem in which most of the food items are laden with lots of pollutants from heavy metals. Soil is said to be the reservoir of nutrients as well as pollutants. These pollutants have been implicated in causing lots of Health issues on human and Animals. Agricultural soil plays major role in food safety, food scarcity and food security, consumption of contaminated foods has serious implication on Human and Animals health. Heavy metals are potential environmental pollutants which are toxic to the human health. When present in an Arable land, they have the ability to bio-accumulate in the soil then to crops and eventually get to humans through food consumption. This study is able to evaluate the effect of heavy metals and risk analysis of arable farmlands in some selected local government areas of southern Taraba state (Donga, Wukari and Takum). All samples were processed, and heavy metals (Pb, Cd, Cr, Hg, and As) concentration were assayed using Atomic Absorption Spectrophotometry (AAS). The results showed that Chromium had a high concentration across all the studied areas with values ranging from 1.40 mg/kg to 2.25 mg/kg. However, Cadmium followed with values ranging from 0.04 mg/kg to 0.07 mg/kg and Arsenic with values ranging from 0.03 mg/kg to 0.06 mg/kg while Lead and Mercury had the lowest concentration of less than 0.03 mg/kg across the three LGAs. Ecological Risk Assessments parameters; Target Cancer Risk, Hazard Index (HI) and Estimated Daily Intake (EDI) were determined to assess the non-carcinogenic health risk. Takum recorded the highest levels of HM having the highest health risk followed by Wukari, whereas Donga had the lowest. Consistent use of crops harvested from the sampled location may pose a serious health challenge; bio-accumulation of toxicants in the soil across the studied areas may pose a health risk due to high concentration of heavy metals which are known to generate free radicals that may lead to oxidative stress and other cellular damages in humans.